El rol del fuego en el Área Ceremonial de Vegachayoq Moqo – Wari (600 d.c.-1000 d.c.): una aproximación a partir del estudio de restos forestales carbonizados y contenedores portátiles. - Ñacari Herreras, Melissa (2020)
ABSTRACT According to the wari stratigraphic sequence, there are up to three moments of defined occupation that go from the early phase to the collapse and definitive abandonment of the city. Each phase is represented by a certain type of architecture that were intentionally covered with very well elaborated fillings and in the different levels of the filling were placed ritual burning contexts. Therefore, the main objective of this work is to know the role of fire in the ceremonial activities of the Vegachayoq Moqo sector. For this, the identification of wood species and study of portable containers was carried out. 670 archaeological charcoals were analyzed, of which four morphological types of Angiosperm wood (Alnus acuminata, Shinus molle, Escallonia resinosa and the fabaceae family) were recognized. After examining the results of the anthracological analysis, it was possible to define that a large percentage of the wood burned in the "D" structure is part of the constructions and the burning contexts associated with the incense were selected because they are high durability fuels. Based on the results of the contextual and anthropological analysis, fire is fulfilling the role of destruction, closure of periods and regeneration preferably in areas where activities of great importance were carried out.